2018
DOI: 10.1111/cas.13553
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive estimation of 10B‐4‐borono‐L‐phenylalanine‐derived boron concentration in tumors by PET using 4‐borono‐2‐18F‐fluoro‐phenylalanine

Abstract: In boron neutron capture therapy (BNCT), 10B‐4‐borono‐L‐phenylalanine (BPA) is commonly used as a 10B carrier. PET using 4‐borono‐2‐18F‐fluoro‐phenylalanine (18F‐FBPA PET) has been performed to estimate boron concentration and predict the therapeutic effects of BNCT; however, the association between tumor uptake of 18F‐FBPA and boron concentration in tumors remains unclear. The present study investigated the transport mechanism of 18F‐FBPA and BPA, and evaluated the utility of 18F‐FBPA PET in predicting boron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…All cells were maintained at 37°C in a humidified incubator containing 5% CO 2 and were washed with phosphate-buffered saline (PBS) and harvested with trypsin as necessary. LAT1 expression of these cells were confirmed in previous studies [16,23].…”
Section: In Vitro Cellular Uptake and Inhibition Assaysupporting
confidence: 85%
“…All cells were maintained at 37°C in a humidified incubator containing 5% CO 2 and were washed with phosphate-buffered saline (PBS) and harvested with trypsin as necessary. LAT1 expression of these cells were confirmed in previous studies [16,23].…”
Section: In Vitro Cellular Uptake and Inhibition Assaysupporting
confidence: 85%
“…The functions of the different transporters (ATB 0,+ , LAT1, and LAT2) in BPA uptake has been evaluated by high-performance liquid chromatography [19]. Furthermore, (18)F-BPA is also a substrate of LAT1 and shows comparable transport ability with BPA into the tumors, and tissue boron concentration of BPA can be quantitatively estimated using L-[(18)F]BPA/PET [20][21][22][23].…”
Section: Second-generation Boron Compoundsmentioning
confidence: 99%
“…Moreover, differences arising from the type of 18 FBPA administration method used were studied. Yoshimoto and colleagues compared the pharmacokinetics of 18 FBPA administered by bolus intravenous injection and continuous intravenous injection using various tumor models, including glioma cells, and found a correlation between the uptake of 18 FBPA to the tumor administered by bolus and continuous injection methods [12].…”
Section: Development Of 18 Fbpa Petmentioning
confidence: 99%
“…The calculation of the 10 B concentration based on 18 FBPA PET data has not yet been completely resolved. Certainly, some animal studies have revealed that the 10 B concentration arising from a therapeutic dose can be predicted using PET and that the results for intravenous bolus and continuous injection are correlated [9,12], and the 10 B concentration in normal tissue can be predicted using a kinetic analysis in humans [18]. However, some concerns remain regarding how accurately a small amount of 18 FBPA accumulation can reflect the 10 B concentration of BPA in the tumor and surrounding normal tissues when a continuous injection for 1 h or more is performed in humans.…”
Section: Clinical Assessment Of 18 Fbpa Petmentioning
confidence: 99%